2013
DOI: 10.1073/pnas.1319582110
|View full text |Cite
|
Sign up to set email alerts
|

ABCC6 prevents ectopic mineralization seen in pseudoxanthoma elasticum by inducing cellular nucleotide release

Abstract: Pseudoxanthoma elasticum (PXE) is an autosomal recessive disease characterized by progressive ectopic mineralization of the skin, eyes, and arteries, for which no effective treatment exists. PXE is caused by inactivating mutations in the gene encoding ATPbinding cassette sub-family C member 6 (ABCC6), an ATP-dependent efflux transporter present mainly in the liver. Abcc6 −/− mice have been instrumental in demonstrating that PXE is a metabolic disease caused by the absence of an unknown factor in the circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
319
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(334 citation statements)
references
References 54 publications
10
319
1
4
Order By: Relevance
“…It is indeed possible that, once secreted in the extracellular space, the ABCC6 substrates may act as autocrine factors promoting the expression of anti-mineralization genes and downregulating the expression of pro-mineralization genes. In agreement with this hypothesis, it was recently reported that cells overexpressing ABCC6 secrete an unidentified substrate that in turn induces a large efflux of nucleotide triphosphates providing the extracellular pyrophosphate, a potent inhibitor of mineralization [29]. Alternatively, it can be hypothesized that ABCC6 deficiency leads to an Brought to you by | MIT Libraries Authenticated Download Date | 5/13/18 10:37 AM intracellular increase of substrates that might modulate the expression of genes involved in mineralization processes.…”
Section: Resultsmentioning
confidence: 77%
“…It is indeed possible that, once secreted in the extracellular space, the ABCC6 substrates may act as autocrine factors promoting the expression of anti-mineralization genes and downregulating the expression of pro-mineralization genes. In agreement with this hypothesis, it was recently reported that cells overexpressing ABCC6 secrete an unidentified substrate that in turn induces a large efflux of nucleotide triphosphates providing the extracellular pyrophosphate, a potent inhibitor of mineralization [29]. Alternatively, it can be hypothesized that ABCC6 deficiency leads to an Brought to you by | MIT Libraries Authenticated Download Date | 5/13/18 10:37 AM intracellular increase of substrates that might modulate the expression of genes involved in mineralization processes.…”
Section: Resultsmentioning
confidence: 77%
“…Pseudoxanthoma elasticum is an autosomal recessive condition characterised by reduced plasma pyrophosphate levels and progressive ectopic mineralisation of the skin, eyes and arteries [91][92][93]. It is primarily caused by inactivating mutations in the ATP-binding cassette subfamily C member 6 (ABCC6) gene [94].…”
Section: Pyrophosphate and Pseudoxanthoma Elasticummentioning
confidence: 99%
“…ABCC6 is primarily expressed in the liver and mediates ATP release from hepatocytes. Abcc6 -/-knockout animals exhibit the symptoms of pseudoxanthoma elasticum and display a 40% reduction in plasma pyrophosphate levels [91]. Studies using these animals have suggested that ATP release is impaired in cells lacking ABCC6 and that the lack of substrate for NPP1 results in lower circulating pyrophosphate levels and the development of pseudoxanthoma elasticum [66].…”
Section: Pyrophosphate and Pseudoxanthoma Elasticummentioning
confidence: 99%
“…Psödoksantoma elastikum (PKE), elastik fibrillerde kalsifikasyon nedeniyle, özellikle deri, gözün Bruch membranı ve kan damarlarında hasara neden olan multisistemik ve metabolik bir bağ dokusu hastalığıdır (1)(2)(3)(4). Otozomal resesif yolla kalıtılır (5).…”
Section: Introductionunclassified